Factors Influencing Banking Customers for Adopting Green Banking - Raju, Jeena; V. Sitharathasankar (International Journal of Psychosocial Rehabilitation, 2019)
Green Banking is also called as ethical banking. It helps to go green in banking activities like mobile banking, internet banking, Net banking and telephonic banking. It is also called as sustainable banking by reducing carbon footprint from the banking activities and helps to protect environment. Green banking was introduced in 2003 and SBI was the first commercial bank which introduced Green Banking strategy in India in the year 2007 to overcome global warming and climate change. Slowly from 2007 all other countries took over the concept of Green banking in their banking activities. The main aim of the study is to analyze various factors influencing banking Customers in adoption of green banking. The main factors included in the study is up gradation of new equipment’s, sufficient installation of machines, attitudes of Bankers customer in handling customers, educating customers in using Green banking. 9 variables are used in the study they are Banks are up - to - date with equipment & technology, banks has Sufficient number of ATM machines, Cash counting machines, Banking staff as “polite, friendly and cooperative, Token machines installed in banks, customers’ requests are handled promptly, banks provide instant solution for Problems faced by customers, Brochures to educate Customers online customer feedback services. 5 point Likert scale and Simple random sampling was used to collect the data. The total sample size collected is 100 Banking customers from Bangalore District. Google form was used to collect the data from banking customers. The study proves that Factors like upgradation of new equipment’s, sufficient installation of machines, attitudes of Bankers customer in handling customers, educating customers in using Green banking has significant association between adoption of green banking. This shows that up gradation of new machines was greater impact on adoption of green banking. The biggest drawbacks of the banks that the banking employees attitude and behaviors towards banking customers is crucial issues and most of the customers has complained that banking employees attitude should be changed and should give severe punishment for misbehaving with the customers. If the banks need to survive in this challenging world it should go beyond the expectation of customer preference.